Making History in Q Henry V [with illustrations]. (12th September 2013) - Mulready, Cyrus
Abstract : This essay argues that The Chronicle History of Henry the Fifth (published in quarto in 1600, 1602, and 1619) was an abbreviated version of Shakespeare's play prepared for a readership interested in chronicle abridgments and other genres of history books. Critical consensus now identifies the Quarto, less than half the length of the Folio version we read and see performed today, as a reduced text prepared for the theater. This essay considers a range of materials that contest this performance hypothesis: abridged chronicles, popular histories, news reports, as well as title‐pages and paratextual matter from other books based on British history. By situating the early quartos of Henry V with these lesser known products of the London book market, I show that early modern publishers and authors shaped a variety of play texts as "chronicle histories" in order to introduce them to a broader market of readers. What emerges from analysis of this evidence is a different view of Q Henry V : a playbook that owes its existence not to theatrical abridgment, but to reader demand for history books, a genre that Q Henry V helped to redefine. (C. M.)